The Effect of Tax Knowledge on Voluntary Tax Compliance with Trust as a Mediating Variable: A Study on Micro, Small, and Medium Enterprises (MSMEs) - Farah Nisa Ul Albab; Eko Suwardi (The Indonesian Journal of Accounting Research, 2021)
One of the determinants of tax compliance is tax. Tax rules often change according to certain conditions. This study examines the role of tax knowledge on volunteer compliance and trust as an intervention variable. The Slippery Slope Framework by Kirchler et al. (2008) was used as the framework of this study. Using a survey method using a questionnaire, this study uses a sample of 108 entrepreneurs belonging to Micro, Small, and Medium Enterprises (MSMEs) in the Special Region of Yogyakarta. The data analysis technique used is SEM-PLS. The test results show that tax compliance and trust are influenced by tax knowledge. The results of the study also show that tax knowledge increases trust. Our research also finds that trust partially mediates the effect of knowledge on voluntary taxation. The results of this study indicate the importance of knowledge and trust of taxpayers to improve voluntary tax compliance.